Synthesis of New Quinazoline-4-One Compounds of Medicinal Importance - R.K. Kawadkar, Ms.; Ghiya, B.J. (Asian Journal of Chemistry, 2010)
Some new quinazoline-4-ons (II-VII) have been synthesised using different amino compounds, viz., ammonia, hydrazine hydrate, urea, thiourea, formamide, guanidine carbonate, etc., with different oxo-compounds. Further condensations of these quinazolines were carried out using piperazine formaldehyde or phenyl isothiocyanate. All the compounds were purified and the structure of the products has been established by elemental analysis and spectral data. (IR, 1H NMR). Significant antimicrobial activities were observed for some members of the series.